2012
DOI: 10.1007/s00439-011-1137-z
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the genetic component of systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a severe connective tissue disorder characterized by extensive fibrosis, vascular damage, and autoimmune events. During the last years, the number of genetic markers convincingly associated with SSc has exponentially increased. In this report, we aim to offer an updated review of the classical and novel genetic associations with SSc, analyzing the firmest and replicated signals within HLA and non-HLA genes, identified by both candidate gene and genome-wide association (GWA) studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 141 publications
1
50
0
Order By: Relevance
“…4,6 To date, genetic risk factors for sclerotic GVHD have not been well defined, but candidate gene and genome-wide association studies have identified single-nucleotide polymorphisms (SNPs) associated with systemic sclerosis. 7 These SNPs include HLA and non-HLA variants involved in adaptive and innate immune responses. We hypothesized that the same SNPs might also have associations with the development of sclerosis in patients with chronic GVHD if the two diseases have similar pathogenic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 To date, genetic risk factors for sclerotic GVHD have not been well defined, but candidate gene and genome-wide association studies have identified single-nucleotide polymorphisms (SNPs) associated with systemic sclerosis. 7 These SNPs include HLA and non-HLA variants involved in adaptive and innate immune responses. We hypothesized that the same SNPs might also have associations with the development of sclerosis in patients with chronic GVHD if the two diseases have similar pathogenic mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In sarcoidosis the development of irreversible lung fibrosis, seen in 10–20% of patients, is associated with poorer quality of life, the need for long-term treatment and a worse prognosis 8. A small number of genes associated with the development of lung fibrosis in the context of SSc9 or of sarcoidosis10–12 have been reported, highlighting a genetic component likely to involve several genes with small individual effects. Although SSc-associated interstitial lung disease (SSc-ILD) and pulmonary sarcoidosis differ from IPF in many respects, including better survival for equivalent disease severity,13 there are many similarities in the fibrotic process and alveolar epithelium abnormalities occur in all three diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, part of the genetic component is shared among different immune disorders, suggesting that these pathologies may be influenced by disease-specific and common molecular pathways 1–4. For instance, most of the genetic associations described for systemic sclerosis (SSc), a fibrotic autoimmune disease of skin and internal organs, have also been reported to play a role in the susceptibility to systemic lupus erythematosus (SLE) 5 6…”
Section: Introductionmentioning
confidence: 99%